Optimizing Fruit Growth in Cherry Tomato (Solanum lycopersicum): A Zeolite LTA Mass Approach - Norsuhailizah, Sazali; Zawati, Harun; Norazlianie, Sazali; Afdhal, Junaidi (Akademi Baru, 2023)
Cherry tomatoes are highly regarded for their exceptional taste and versatility, receiving recognition in both the field of horticulture and culinary arts. This study examines the importance of zeolite LTA mass as a growth medium in enhancing cherry tomato cultivation in terms of productivity and sustainability. This research was conducted to investigate the effects of incorporating zeolite LTA into the growth substrate on fruit weight. The experiments were designed systematically. The critical metrics undergo thorough measurement and detailed analysis after an 8 and 12-week cultivation period. Our study reveals a clear correlation between the mass of zeolite LTA and the growth of cherry tomato plants. The inclusion of zeolite LTA as a growth substrate has a significant positive impact. The cherry tomato plants treated with this innovative method show significant growth of size fruits weighing up to 104.55 grams. This study demonstrates the potential of using zeolite LTA mass as a growth medium for cherry tomato cultivation, going beyond conventional methods. Furthermore, it enhances our understanding of the complex mechanisms involved in this phenomenon, paving the way for the development of sustainable and efficient horticultural practices. In conclusion, this study is a pioneering contribution to the field of crop science, highlighting the significant impact of using zeolite LTA mass as a growth medium to maximize cherry tomato yields. Moreover, it encourages further investigations into the various uses of zeolites in plant cultivation, highlighting the importance of adopting environmentally conscious approaches in modern agriculture.